Measurement of the polarization amplitudes in B0 → J/ψK*(892)0 decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
An analysis of the decay B0→J/ψK∗(892)0 is presented using data, corresponding to an integrated luminosity of 1.0 fb−1, collected in pp collisions at a center-of-mass energy of 7 TeV with the LHCb detector. The polarization amplitudes and the corresponding phases are measured to be |A∥|2=0.227±0.004 (stat)±0.011 (syst), |A⊥|2=0.201±0.004 (stat)±0.008 (syst), δ∥[rad]=−2.94±0.02 (stat)±0.03 (syst), and δ⊥[rad]=2.94±0.02 (stat)±0.02 (syst). Comparing B0→J/ψK∗(892)0 and B̄0→J/ψK̄∗(892)0 decays, no evidence for direct CP violation is found.
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 598
Im Titel ist "0" hochgestellt
Gesehen am 27.04.2021